Implementasi Metode Takror Dalam Pembelajaran Bahasa Arab Di Madrasah Ibtidaiyah Miftahul Abidin Surabaya - Zainal Arifin (TADARUS, 2015)
This research is motivated by some problems, the first is the low quality of education and the second is the gap of science knowledge in Indonesia. This study aims to determine what method takror meaning, how Takror implementation of methods Takror in learning Arabic at at madrasah ibtidaiyah miftahul abidin Surabaya, nnything supporting and inhibiting factors in implementating of methods Takror in learning arabic at at madrasah ibtidaiyah miftahul abidin surabaya. The method used in this research is field research with qualitative naturalistic descriptive, and case study approach of the research is descriptive; explained; interpreted the data, then generate descriptive data that is behaviours and words written or spoken of people that can be observed. whereas the results of the data analysis presented in a narrative descriptive form, which occurs naturally just the way it is, and in a normal situation that is not manipulated circumstances and condition. Technique data collecting is done by observation, interviews and documentation. Data analysis techniques in this research is descriptive qualitative inductive. While the techniques used in checking the validity of the data is an extension of the participation, persistence observation, triangulation, examination peers through discussion. The triangulation techniques used by researchers is the triangulation of data, methods, and resources. The results of this study can be concluded that Madrasah Ibtidaiyah Miftahul Abidin Surabaya has implemented Takror methods in learning arabic well, and in accordance with the principles and steps that exist. There are factors supporting the implementation of Takror method in learning Arabic at Madrasah Ibtidaiyah Miftahul Abidin Surabaya, the suitability of Arabic material to the method taht is used, the support of the principal, teachers and their students' learning interest. There is also a inhabitting factor in implementating Takror methods in Arabic learning at Madrasah Ibtidaiyah Miftahul Abidin Surabaya, namely the lack of time allocation that is the two meetings in one week with a duration of 80 minutes, sometimes causes the result of Takror is less than optimal results. Speaking skill that uneven on all students sometimes make students less confident when issuing argument.